THE EFFECT OF LIQUIDITY AND PROFITABILITY ON COMPANY VALUE (Study on consumer goods industry sector companies in the food and beverage sub-sector listed on the IDX in 2018-2019) - Joseph Andre Sinaga; Harman Malau (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
This study aims to determine whether liquidity and profitability influence firm value. The data used in this study is secondary data where this secondary data is taken from the financial statements of companies in the consumer goods industry sector in the food and beverage sub-sector listed on the IDX in 2018-2019. This research uses descriptive analysis method, linear regression, and significant test. The results of this study indicate that liquidity has an influence on firm value in the consumer goods industry sector in the food and beverage sub-sector. Same thing with profitability. Profitability influences firm value. And after conducting the simultaneous test, liquidity, and profitability influence firm value, but not significant.